Governing The Ombudsman As An Independent State Institution In The Constitution: An Attempt To Strengthen Public Service Supervision In Indonesia - Putra, Rizki; Taufiqurrohman, Moch. Marsa; Pambudi, Bima Rico (Al-Daulah : Journal of Criminal Law and State Administration Law, 2022)
This article aims to examine the urgency and the probability of regulating the Ombudsman in the constitution, as an effort to strengthen the supervision of public services in Indonesia. This article finds that the existence of an Ombudsman is important to oversee excellent public services, as this is part of Human Rights. However, the supervision of the Ombudsman in Indonesia is not strong enough to guarantee a truly complete public service. By using the doctrinal normative juridical research method in collaboration with the Reform Oriented Research method, the statutory, conceptual, and case approach, this article finds that in addition to the executive, judicial, and legislative institutions, there is a fourth branch of power that accommodates the existence of independent state institutions such as the Ombudsman. After trying to compare the Ombudsman regulations in South Africa and Thailand, this article offers to legitimize the Ombudsman philosophically and politically in the constitution, as a form of guarantee for the implementation of excellent public services. Keywords: Constitutional Amendment; Ombudsman; Public Service